PSYCHOLOGICAL RESILIENCE IN CHRONIC ILLNESS: COPING MECHANISMS AND EMOTIONAL ADJUSTMENT - Asma Iqbal (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Chronic illnesses, including diseases such as diabetes, cardiovascular diseases, and cancer, profoundly impact the psychological well-being of individuals. Psychological resilience—the ability to adapt to adversity—plays a critical role in coping with the emotional and psychological challenges of chronic illnesses. This article explores the coping mechanisms and emotional adjustment processes that contribute to psychological resilience in individuals facing chronic illnesses. By examining the interplay between individual coping strategies and resilience, this article highlights the importance of psychological support in fostering emotional well-being and long-term health outcomes. This study identifies key coping mechanisms, such as social support, cognitive reframing, and mindfulness, and discusses their effectiveness in enhancing resilience. It explores how cultural factors and socio-economic conditions in Pakistan influence emotional adjustment to chronic illness.